The Nucleocapsid Protein of Potato Yellow dwarf Virus: Protein Interactions and Nuclear Import Mediated by a Non-Canonical Nuclear Localization Signal - Anderson, Gavin; Wang, Renyuan; Bandyopadhyay, Anindya; Goodin, Michael (Frontiers in Plant Science, 2012)
Potato yellow dwarf virus (PYDV) is the type species of the genus Nucleorhabdovirus and, like all members of this genus, replication and morphogenesis occurs inside the nuclei of infected cells. Protein localization prediction algorithms failed to identify a nuclear localization signal (NLS) in PYDV nucleocapsid (N) protein, although PYDV-N has been shown to localize exclusively to the nucleus when expressed as a GFP:N fusion in plant cells. Deletion analysis using fragments of PYDV-N identified a karyophillic region in the carboxy-terminal 122 amino acids. Alanine-scanning mutagenesis was performed across this region in the context of the full-length N protein. Mutants were assayed for their ability to nuclear localize using live-cell imaging and a yeast-based assay. Two amino acid motifs, 419QKR421 and 432KR433 were shown to be essential for nuclear import and interaction with importin-α. Additional bimolecular fluorescence complementation (BiFC) showed that the PYDV-N NLS mutants cannot be ferried into the nucleus via interaction with PYDV-P or -M. In contrast, interaction with N NLS mutants appeared to retard the nuclear import of PYDV-P. GFP fused to aa 419-434 established that the PYDV-N-NLS can function outside the context of this protein. Taken together, it was determined that PYDV-N contains the bipartite NLS 419QKRANEEAPPAAQKR433.